Pharmacological screening of heartwood of Pterocarpus marsupium Roxb in stress induced neurobehavioral changes in albino Wistar rat - Vrushali Dongare; Swati Kolhe (Brain Disorders)
Stress can be brief and situational, serving as a positive motivator for performance. However, prolonged stress can lead to chronic stress, negatively impacting health and wellbeing. This study evaluated the therapeutic effects of Pterocarpus marsupium Roxb. on stress-induced neurobehavioral changes in albino Wistar rats. Locomotor activity, anxiety, and memory were assessed in offspring treated with P. marsupium (200, 300, 500 mg/kg) or diazepam from postnatal day 21, including control and stress-induced groups.Results showed that treatment with P. marsupium at 500 mg/kg significantly enhanced locomotor activity compared to the stress-induced group (p < 0.05). The elevated plus maze test showed a significant reduction in anxiety-related behaviors at 500 mg/kg of P. marsupium, with time spent in the open arms significantly increased (p < 0.01) compared to stressed controls. This study highlighted its therapeutic potential, supported by DPPH assay-proven antioxidant activity, on stress-induced neurobehavioral changes in albino Wistar rats. Notably, the P. marsupium showed significant modulatory effects on stress hormones and oxidative stress. Cortisol levels were significantly suppressed in P. marsupium treated groups compared to the stress-induced group (p < 0.01) and decreased the amount of thiobarbituric acid reactive substances (TBARS) in the brain. These findings reveal the neuroprotective potential of P. marsupium against stress, suggesting its promise for future treatments for anxiety and depression, pending further research. This study contributes to the expanding knowledge of natural compounds for ameliorating complex neurobehavioral changes and highlights the necessity of multi-faceted approaches to address their intricate manifestation.